Perancangan Sistem Penerimaan Murid Baru dengan Fitur Informasi Sekolah Berbasis Web pada Madrasah Tsanawiyah Al Azhar Kalijaya - Riski Yudhi Prasongko; Dimas Dahari (Jurnal Publikasi Teknik Informatika, 2025)
X has not yet implemented a web-based information system to serve as a school information medium and support the New Student Admission (PPDB) process. Previously, registration was carried out manually through brochures and Google Forms, which were less effective and difficult to manage. This study aims to design and develop a web-based PPDB system integrated with school information to improve administrative efficiency and provide convenience for prospective students. The development method used was the prototype model, which included stages of design, development, evaluation, and implementation. The system was developed using the CodeIgniter 4 framework, AdminLTE template, and MySQL database. The system development process involved creating a user-friendly interface for prospective students to easily register and access school information online. Additionally, it supports data verification and enables the digital management of student data and school-related information, eliminating the need for manual processing. The results of this study indicate that the developed system is capable of facilitating users in the registration process, ensuring the accuracy and efficiency of data verification, and streamlining the overall management of school information. The system has been successfully tested and evaluated to ensure it meets user requirements and improves administrative tasks. The implementation of this system is expected to enhance the overall experience for prospective students and administrators by reducing errors, improving data accessibility, and increasing efficiency in handling the PPDB process. This web-based solution also provides a more modern and scalable approach to school administration, which can be further developed and adapted for future use. The findings suggest that the integration of web-based systems in educational institutions can significantly improve service delivery and operational management